EVOLUTION ET COMPARAISON DES RENDEMENTS QUANTITATIFS DES RESULTATS AUX EXAMENS D’ETAT DES ECOLES OFFICIELLE ET CONVENTIONNEES CATHOLIQUES DE LA VILLE DE KISANGANI DE 2008 à 2013 « CAS DE L’OPTION MATHEMATIQUE-PHYSIQUE - BAENDAENDA SHINDANI Depse (IJRDO- Journal of Educational Research, 2019)
Evolution and comparison of quantitative yields (out put) of state exams of official and catholic schools in Kisangani town untill 2008 up 2013. The success on the state exams of Maths, the success on superior studies and the learning to work, other disciplines constitut without doupt the most preocupation of all pupils at scientific humanities. It must be important to have knowledge of some definitions and fondamental theorms around which articulate the whole courses, the knowledge of the important results of Maths, the aptitude to the personnal research and knowledge which atlous to make resolution of various problems. In all secondary Teaching Institution which organizes the full cycle, the success to the state exam affects (interest) and always attracts most pupils. Schools which organize the option Maths-physicals in Kisangani have each school year decrease of candidates in relationship to other schools which organize other options as general pedagogy, social… The misssing of library, laboratories, and the appropriate training of Math and adopted in definite official and catholic schools which allow the evolution of sciences and technology have created an empty in the mind of pupils disorganized the work of teacher. The publication of this work is a hope, because the definite solution in this big problem require coherent and global pedagogical look after. In marketing tjis work, our worry is to compare the evolution of the global results to the state exams of the Maths-physical option of catholic and oicial schools inKisangani town between 2008-2018 and ater to compare their quantitative yields.